The effect of tax avoidance and tax risk on firm risk - Andrie Yuwono; Elia Mustikasari (Universitas Hayam Wuruk Perbanas, 2022)
This study aims to determine whether tax avoidance and tax risk have an influence on firm risk. This study uses data in the form of annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2018. The results of this study show that tax avoidance and tax risk have a positive effect on firm risk. The results of this study prove the signaling theory that company management sends signals in the form of information about tax avoidance and tax risk to investors. The investors then use the information as a tool in making decisions in the future.